The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/2162402x.2016.1213931
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunotherapeutic targets by genomic profiling of rectal NET metastases

Abstract: Neuroendocrine tumors (NETs) of the gastrointestinal tract are a rare and heterogeneous group of neoplasms with unique tumor biology and clinical management issues. While surgery is the only curative treatment option in patients with early stage NETs, the optimal management strategy for patients with advanced metastatic NETs is unknown. Based on the tremendous success of immunotherapeutic approaches, we sought to investigate such approaches in a case of metastatic rectal NET. Here, we apply an integrative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…The same study showed mutual association between lymph node invasion, CpG island methylation, and miR-885-5p expression (92). Finally, whole-genome sequencing on six liver metastases from the same patient showed that 11 of 18 somatic mutations were identified in all samples, including known tumor-related genes HSPG2 , SERPINF2 (extracellular matrix remodeling), and SMARCA1 (chromatin remodeling) (93).…”
Section: Basic Histology and Biology Of Gep-nensmentioning
confidence: 99%
“…The same study showed mutual association between lymph node invasion, CpG island methylation, and miR-885-5p expression (92). Finally, whole-genome sequencing on six liver metastases from the same patient showed that 11 of 18 somatic mutations were identified in all samples, including known tumor-related genes HSPG2 , SERPINF2 (extracellular matrix remodeling), and SMARCA1 (chromatin remodeling) (93).…”
Section: Basic Histology and Biology Of Gep-nensmentioning
confidence: 99%
“…However, a mutual association between lymph node invasion, CpG island methylation, and miR-885-5p expression, has been described [142]. Interestingly, wholegenome sequencing of six liver metastases from a rectal NET showed that 11 of 18 somatic mutations were identified in all samples, including known tumor-related genes HSPG2, SERPINF2 (extracellular matrix remodeling), and SMARCA1 (chromatin remodeling) [143]. Recently, repetitive mutations in five genes including TP53, PTEN, CDKN2A, FBXW7, and AKT1 have been described in rectal NETs, the mutational burden seeming to increase with tumor grade [141].…”
Section: Large Bowel and Rectummentioning
confidence: 99%
“…One possible reason is the lack of messages about mechanistic alterations underlying the development of RNET. To date, apart from a handful of studies focusing on the genetic and epigenetic changes in such neoplasms 36 , comprehensive mechanistic characterization is still urgently needed for therapeutic and diagnostic improvement for patients with RNET. To this end, we hereby presented a comprehensive and in-depth study by performing shotgun metagenomic and untargeted metabolomic profiling of faecal samples from RNET and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%